Solid Organic Fertilizer Packaging in Karang Ayu Cattle Group in Ayunan Village, Abiansemal Sub-District, Badung - Ni Made Ayu Gemuh Rasa Astiti; A.A.Rai Sita Laksmi; I Gusti Agung Putu Eryani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Packaging has become increasingly essential. Packaging no longer serves only as a container for wrapping food or beverage products to protect them from dirt, dust, air, impact, and sunlight, but also as a promotional tool that attracts purchasers' attention. Increased income from the marketing of organic fertilizer products produced from cow manure will encourage breeders to increase their cattle population. Consumers will choose products with appealing packaging over those with plain or simple packaging that is unattractive. Cows produce manure that can be processed into organic fertilizer in addition to flesh. In the village of Ayunan, a substantial amount of processed organic fertilizers manufactured from cow manure are produced. The marketing management process for partner-produced organic fertilizer products is extremely constrained, particularly in terms of product packaging, which is crucial to product marketing. The primary issue that will be addressed is how to create attractive packaging that will encourage consumers to purchase products. Presentations, demonstration plots, and direct practice of packaging organic fertilizer products produced by partners are employed. This activity is anticipated to increase breeders' knowledge and their ability to market their products, increasing breeders' income and prosperity.